A qualitative study to understand guideline-discordant use of imaging to stage incident prostate cancer. (December 2015) - Makarov, Danil; Sedlander, Erica; Braithwaite, R.; Sherman, Scott; Zeliadt, Steven; Gross, Cary; Curnyn, Caitlin; Shedlin, Michele
Abstract Background Approximately half of veterans with low-risk prostate cancer receive guideline-discordant imaging. Our objective was to identify and describe (1) physician knowledge, attitudes, and practices related to the use of imaging to stage prostate cancer, (2) patient attitudes and behaviors related to use of imaging, and (3) to compare responses across three VA medical centers (VAMCs). Methods A qualitative approach was used to explore patient and provider knowledge and behaviors relating to the use of imaging. We conducted 39 semi-structured interviews total—including 22 interviews with patients with newly diagnosed with prostate cancer and 17 interviews with physicians caring for them—between September 2014 and July 2015 at three VAMCs representing a spectrum of inappropriate imaging rates. After core theoretical concepts were identified, the Theoretical Domains Framework (TDF) was selected to explore linkages between themes within the dataset and existing domains within the framework. Interviews were audio-recorded, transcribed verbatim, and then coded and analyzed using Nvivo software. Results Themes from patient interviews were categorized within four TDF domains. Patients reported little interest in staging as compared to disease treatment (goals ), and many could not remember if they had imaging at all (knowledge ). Patients tended to trust their doctor to make decisions about appropriate tests (beliefs about capabilities ). Some patients expressed a minor concern for radiation exposure, but anxiety about cancer outcomes outweighed these fears (emotion ). Themes from physician interviews were categorized within five TDF domains. Most physicians self-reported that they know and trust imaging guidelines (knowledge ) yet some were still likely to follow their own intuition, whether due to clinical suspicion or years of experience (beliefs about capabilities ). Additionally, physicians reported that medico-legal concerns, fear of missing associated diagnoses (beliefs about consequences ), influence from colleagues who image frequently (social influences ), and the facility where they practice influences rates of imaging (environmental context ). Conclusions Interviews with patients and physicians suggest that physicians are the primary (and in some cases only) decision-makers regarding staging imaging for prostate cancer. This finding suggests a physician-targeted intervention may be the most effective strategy to improve guideline-concordant prostate cancer imaging.